Repair Bond Strength of Composite Resin to Aged Resin and Glass-Matrix CAD/CAM Ceramic Materials Using Two Different Repair Systems - Sarah Alnafaiy (MDPI AG, 2021)
This study evaluates the repair bond strength of resin-matrix and glass-matrix CAD/CAM ceramic materials based on two repair systems. Thirty specimens measuring 2.5 mm in thickness were prepared from Crystal Ultra (CU), Vita Enamic (EN), Lava Ultimate (LU), Cerasmart (CS), and Vitablocs Mark II (VM2) materials and aged for 5000 thermal cycles. Specimens were randomly allocated into three groups: control, Monobond-S (MS) primer, and Monobond Etch & Prime (MEP). Composite resin (Tetric N Ceram) (5 mm in diameter and 2 mm thick) was packed and light-cured onto treated specimen surfaces. Subsequently, the specimens’ shear bond strength (SBS) was evaluated, and failure modes was recorded. Statistical analysis was performed using factorial ANOVA and Tukey’s post hoc tests (a = 0.05). The factorial ANOVA revealed significant interactions between the material type and repair system, which was significant (p < 0.01). The highest and lowest SBS were obtained for CU (27.09 ± 1.11) and VM2 (4.30 ± 0.59) in MS and control groups, respectively. In all the groups, CU demonstrated higher SBS, whereas VM2 demonstrated lower SBS. There were no significant differences in SBS between EN and LU, and CS and CU in all the study groups (p > 0.05). The Monobond-S repair system provided non-significantly higher SBS compared to the MEP systems, except for VM2 and LU materials. The new resin-matrix CAD/CAM material demonstrated the highest SBS compared to the other materials for both conventional and MEP repair systems. Both repair systems showed clinically acceptable bond strength and allowed for successful repair of the resin-matrix ceramic materials.